LYMPHOPENIA AS A FACTOR INVOLVED IN THE AUTOIMMUNITY DEVELOPMENT IN MURINE GRAFT VS. HOST DISEASE - E. V. Goiman; V. O. Tkachev; O. T. Kudayeva; O. P. Kolesnikova; V. A. Kozlov (Acta Biomedica Scientifica)
Syngeneic splenocyte transplantation leads to lymphopenia development in intact mice owing to decreased proliferative activity of bone marrow hematopoietic progenitor cells. In the mice with induced chronic graft-versus-host disease (cGVHD) transfer of syngeneic lymphocytes has little or no effect on the level of already existing lymphopenia, but increases its duration. These results are in close agreement with the received evidences that transfer of syngeneic cells increases frequency of autoimmune glomerulonephritis at cGVHD. Thus, results of research speak in favor of conclusion that lymphopenia and initiated by it homeostatic proliferation play a pathogenetic role in the development of autoimmune reactions at cGVHD.